Unplanned urbanization and health risks of Dhaka City in Bangladesh: uncovering the associations between urban environment and public health - Rahaman, Mohammad Anisur; Kalam, Abul; Al-Mamun, Md. (Frontiers in Public Health, 2023)
Background Dhaka City, the capital of Bangladesh, has experienced rapid and unplanned urbanization over the past few decades. This process has brought significant challenges to public health as the urban environment has become a breeding ground for various health risks. Understanding the associations between unplanned urbanization, the urban environment, and public health in Dhaka City is crucial for developing effective interventions and policies. Objectives This review paper aims to uncover the associations between unplanned urbanization and health risks in Dhaka City, with a specific focus on the urban environment and its impact on public health. The objectives of this study are to examine the health challenges faced by the city’s population, explore the specific urban environmental factors contributing to health risks, analyze the socioeconomic determinants of health in unplanned urban areas, evaluate existing policies and governance structures, identify research and data gaps, and provide recommendations for future interventions. Methods A comprehensive literature review was conducted to gather relevant studies, articles, reports, and policy documents related to unplanned urbanization, the urban environment, and public health in Dhaka City. Various databases and online resources were searched, and the selected literature was critically analyzed to extract key findings and insights. Results The findings reveal that unplanned urbanization in Dhaka City has led to a range of public health risks, including air pollution, inadequate water and sanitation, poor waste management, overcrowding, slums, and substandard housing conditions. These environmental factors are strongly associated with respiratory diseases, waterborne illnesses, and other adverse health outcomes. Socioeconomic determinants such as poverty, income inequality, and limited access to healthcare further exacerbate the health risks faced by the urban population. Conclusion Unplanned urbanization in Dhaka City has significant implications for public health. Addressing the associations between unplanned urbanization, the urban environment, and public health requires comprehensive policies and interventions. Improved urban planning, enhanced infrastructure, and better policy governance are essential for mitigating health risks. Furthermore, addressing socioeconomic disparities and ensuring equitable access to healthcare services are crucial components of effective interventions.